IDENTIFIKASI PENGEMBANGAN WILAYAH KABUPATEN-KABUPATEN ANGGOTA LEMBAGA REGIONAL BARLINGMASCAKEB - Gunawan, Diah Setyorini; Gunawan, Ratna Setyawati (Jurnal Ekonomi & Studi Pembangunan, 2008)
This study aims, first, identify the economic position of each district in terms of economic growth and Barlingmascakeb per capita income level. Second, identify the dominant different districts of the economic structure Barlingmascakeb. Third, Identify differences in the economic structure of the district members Barlingmascakeb. This study used the period 1995-2002, secondary data consisting of regional gross domestic product (GDP), including oil and gas on the basis of constant prices of 1993, Fourthly, identify the districts that have the most advantageous position in terms of levels of accessibility. This study uses secondary data for the period 1995-2002, which consists of gross regional domestic product (GRDP), including oil and gas based on constant prices of 1993, total population, distance inter district/city, number of tourists housed in hotels, the amount of bus company and the number of vehicles, number of hotel. This research uses Klassen typology analysis, growth models (MRP) analysis, the location quotient analysis (LQ), Divergence Index Krugman analysis, and connectivity analysis quotient data (CQ). The results of the study, Cilacap is included in the classification of fast forward and fast-growing. Purbalingga included in the classification of areas of rapid growth. District Banjarnegara, Banyumas and Kebumen district included in the classification of relatively left behind areas.